UPAYA PEMERINTAH DALAM MENINGKATKAN PEMENUHAN PREDIKAT NINDYA KOTA LAYAK ANAK DI KOTA GORONTALO - Mokodongan, Regi; Van Gobel, Lisda; Al-Hadar, Sofyan (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to analyze the efforts of the Gorontalo City Government in achieving the Nindya predicate for Child-Friendly City (CFC). The research focuses on three key aspects: inter-agency coordination among Local Government Organizations (OPD) and stakeholders, the implementation of program evaluation, and the availability of supporting budget. A qualitative approach with descriptive methods was applied. Data were collected through in-depth interviews with key informants such as the head of the agency, secretary, department heads, financial division, and community figures. The results show that the local government has formed a CFC Task Force and conducted cross-sectoral coordination. However, community and private sector participation remains limited. Program evaluation is carried out periodically but tends to emphasize administrative procedures rather than measuring the actual impact on children. Budget constraints are still a major challenge, as there is no dedicated allocation for CFC programs. Based on these findings, it is recommended that the government strengthen participatory coordination, improve impact-based evaluation systems, and advocate for thematic budget allocation to ensure the sustainability of CFC initiatives.